Microbiological quality evaluation of fried rice sold at food premises in Kuantan city, Pahang - Abu Bakar, Ibrahim; Abdul Rafa, Ainin Azwani; Abdullah Sani, Norrakiah (IIUM Press, International Islamic University Malaysia, 2018)
Food contamination is a crucial health problem as it could result in food-borne illness. This research aimed to evaluate the microbiological quality of ready-to-eat (RTE) fried rice dishes sold at different type of food premises in Kuantan city, Pahang. Total Plate Count (TPC), Staphylococcus aureus, Bacillus cereus and Aeromonas spp. bacteria were used as microbiological contamination indicators. About 52 samples were collected stratified randomly from four types of food premises (restaurant, cafeteria, food stall and night market) where about 13 samples were respectively collected from each type of the food premises. The results showed that TPC had medium mean count (6.30x105±1.47x105 cfu/g), S. aureus and B. cereus had high mean counts (7.70x104±2.22x105 cfu/g and 3.85x105±1.67x106 cfu/g respectively), while Aeromonas spp. had medium mean count (7.13x104±2.42x105 cfu/g). The mean counts of TPC in the samples collected from cafeteria were highest compare to other food premises.